The Puteri Aisyiyah Orphanage Development at Banua Anyar - Farahdita Rahmi; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah (Universitas Lambung Mangkurat, 2023)
An orphanage is a social institution that protects and guides orphans, orphans, neglected and poor people for the welfare of foster children. Orphanages also have an essential role in educating and fostering foster children so that their behaviour can be controlled. This article describes strengthening character building through religious, social, skills and health guidance at the Puteri Aisyiyah Orphanage, Banua Anyar Village. The focus of the service participants was the children of the Puteri Aisyiyah Orphanage, Banua Anyar Village. Guidance is carried out by delivering material related to religion, social skills and health. Guidance is carried out every Sunday on 07, 14, 21 and 28 May 2023. The results of the dedication are presented, namely the problems we encountered, including a lack of character guidance carried out by caregivers for the children of the Puteri Aisyiyah Orphanage, considering that in this era, there are many cultures outsiders are coming in and of course, the younger generation must be able to filter out what is good and what is wrong. So that character building can form a person who is more ready to face future challenges. Community service as a concrete step is a form of social care from the Social Studies Education Department FKIP ULM.